Comparing methods for glomerular filtration rate estimation - Xiaoqian Zhu; Tariq Shafi; Keith C. Norris; Jeannette Simino; Srishti Shrestha; Thomas H. Mosley; Michael E. Griswold; Seth T. Lirette (Journal of Clinical and Translational Science, 2025)
Abstract